A survey of antibiotic resistance in Streptococcus pneumoniae and Haemophilus influenzae in Turkey, 2004-2005 - DURMUŞOĞLU, LÜTFİYE (OXFORD UNIV PRESS, 2007)
Objectives: To determine the prevalence of antimicrobial resistance among Streptococcus pneumoniae and Haemophilus influenzae isolated in Turkey as part of Survey Of Antibiotic Resistance, a surveillance programme in the Africa and Middle East region examining the antimicrobial susceptibility of key bacterial pathogens involved in community-acquired respiratory tract infections (CARTIs). Methods: Susceptibility was evaluated against a range of antimicrobial agents using disc diffusion and Etest methods. Results: Six centres in five cities collected 301 S. pneumoniae and 379 H. influenzae isolates between October 2004 and November 2005. Among S. pneumoniae, the prevalence of isolates with intermediate susceptibility (MICs 0.12-1 mg/L) and resistance to penicillin (MICs >= 2 mg/L) was 24.6% and 7.6%, respectively; there was a wide variation between cities (2.4% to 36.9% intermediate and 0% to 23.8% resistant phenotypes). Macrolide-azalide resistance rates exceeded those of penicillin resistance in all cities. Overall, 5.0% of isolates were co-resistant to penicillin and erythromycin and 10.0% were multidrug-resistant ( joint resistance to erythromycin, co-trimoxazole and tetracycline). Agents tested to which over 90% of countrywide S. pneumoniae isolates remained susceptible were amoxicillin/clavulanate ( 98.7%), chloramphenicol (94.7%) and cefprozil (90.6%). Overall, the percentage of H. influenzae isolates producing beta-lactamase was 5.5%, differing widely across the country with the highest prevalence of b-lactamase production detected in Trabzon (14.0%) and no beta-lactamase-positive isolates found in Izmir. H. influenzae had the highest per cent susceptibility to amoxicillin/clavulanate (99.5%) and ofloxacin (99.2%) while > 20% were resistant to co-trimoxazole. Conclusions: Prevalence of penicillin and macrolide-azalide resistance among S. pneumoniae appears to be on the increase in Turkey while overall beta-lactamase production in H. influenzae remains relatively low. To adequately monitor the spread of drug-resistant phenotypes among these two important CARTI pathogens, ongoing collection of resistance surveillance data is
Keywords: pneumococci; surveillance; community-acquired respiratory tract infections; RESPIRATORY-TRACT INFECTIONS; ANTIMICROBIAL RESISTANCE; MORAXELLA-CATARRHALIS; SURVEILLANCE PROGRAM; SUSCEPTIBILITY; MANAGEMENT; EPIDEMIOLOGY; QUINOLONES; PATHOGENS; BACTERIA